2015
DOI: 10.1002/pbc.25684
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Outcome in Localized Extremity Rhabdomyosarcoma. Pooled Analysis from Four International Cooperative Groups

Abstract: Background Extremity rhabdomyosarcomas do not always show satisfactory outcomes. We analyzed data from 643 patients treated in 14 studies conducted by European and North American groups between 1983 and 2004 to identify factors predictive of outcome. Procedure Clinical factors, including age; histology; site of primary (hand and foot vs. other); size; invasiveness (T stage); nodal involvement (N stage); and treatment factors, including post-surgical group; chemotherapy type and duration; radiotherapy; and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Treatment consists of multimodal therapy including chemotherapy and surgery with or without radiotherapy. A recent meta‐analysis of patients with RMS of the extremity treated within 14 studies reported a 5‐year OS rate of 67% …”
Section: Histology‐specific Nomogramsmentioning
confidence: 99%
“…Treatment consists of multimodal therapy including chemotherapy and surgery with or without radiotherapy. A recent meta‐analysis of patients with RMS of the extremity treated within 14 studies reported a 5‐year OS rate of 67% …”
Section: Histology‐specific Nomogramsmentioning
confidence: 99%
“…European and North American Groups have compared their experience in a series of workshops. The better EFS obtained in COG protocols in some groups of patients including RMS localized in parameningeal or extremity primary sites could be explained by more systematic use of local control measures, and especially radiotherapy. In fact, European groups tried to limit the use of radiotherapy in their trials with the goal of identifying patients who could avoid radiotherapy in an attempt to reduce side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Different protocols developed over the years have gradually reduced the total duration of treatments from the original 2 years without apparently impairing the results, but analyses on particular subgroups of patients would suggest a better outcome for patients treated for longer. 28 On the other hand, the better outcome achieved with the maintenance therapy may relate to the drugs involved, i.e., vinorelbine and/or low-dose cyclophosphamide. Their combined effect may elicit an anti-angiogenic mechanism, killing tumor cells resistant to the standard therapy.…”
Section: Tj Tumori Journalmentioning
confidence: 99%